Mobility Robustness Optimization in LTE-Advanced System - Rongyi Hu; Mugen Peng; Hongyan Zhang; Yuan Li (Dianxin kexue)
Self-optimization network has already become the hotspot of the mobile communication study. With the rapid development of mobile communication technology，mobility robustness has increasingly been focused on by of the users，especially the problems such as the handover failure，users’ dropped calls and poor communication quality of the mobile cellular communication network. In order to improve users’ experience and communication robustness，an algorithm was proposed，by which the mobility robustness was improved and handover parameters were optimized，taking consideration of the characteristics of handover events and different handover failure scenarios like early handover，late handover and ping-pong handover. The rate of users’ dropped call was taken as the performance indicator，and the performances through system-1evel simulation were analyzed. Simulation results show that，owing to the mobility robustness optimization algorithm，dropped call rate is absolutely reduced from 10.9% to 6.2% in the homogeneous network and from 11.3% to 5.3% in the heterogeneous network，and the overall performance has been highly improved.